An End-to-End Secure Patient Information Access Card System - Alkhateeb, A.; Singer, H.; Yakami, M.; Takahashi, T. (Methods of Information in Medicine, 2000)
The rapid development of the Internet and the increasing interest in Internet-based solutions has promoted the idea of creating Internet-based health information applications. This will force a change in the role of IC cards in healthcare card systems from a data carrier to an access key medium. At the Medical Informatics Department of Kyoto University Hospital we are developing a smart card patient information project where patient databases are accessed via the Internet. Strong end-to-end data encryption is performed via Secure Socket Layers, transparent to transmit patient information. The smart card is playing the crucial role of access key to the database: user authentication is performed internally without ever revealing the actual key. For easy acceptance by healthcare professionals, the user interface is integrated as a plug-in for two familiar Web browsers, Netscape Navigator and MS Internet Explorer.
Keywords: Health Information Systems; IC cards; Internet; Security; SSL; Plug-in